In Search of the Ljubljana Cathedral's First Antiphoner - Snoj, Jurij (De musica disserenda, 2017)
The fragments of plainchant manuscripts kept in the Ljubljana archives include the remnants of a two-volume antiphoner and a psalter, written in the same hand. The manuscripts these fragments belonged to followed the rite of Aquileia and they were compiled in the second half of the fifteenth century (or even in the first decades of the sixteenth century); that is, in the period when the chapter of the newly-founded diocese of Ljubljana (1461) began performing plainchant liturgy. The manuscripts were destroyed in the second half of the seventeenth century, when the Roman rite replaced the Aquileian rite in the Ljubljana diocese. Thus it seems very likely that they are remnants of the first antiphoner and psalter of the Ljubljana cathedral.